Experiments on an integrated aquaculture system (seaweeds and marine fish) on the Red Sea coast of Saudi Arabia: efficiency comparison of two local seaweed species for nutrient biofiltration and production - Yousef S. Al‐Hafedh; Aftab Alam; Alejandro H. Buschmann; Kevin M. Fitzsimmons (Reviews in Aquaculture, 2012)
Seaweeds absorb inorganic nutrient wastes from mariculture and reduce their undesirable environmental effects. Mariculture in Saudi Arabia is increasing rapidly, thus, to exploit aquaculture wastes and to reduce coastal pollution risks, local seaweeds were cultured using mariculture effluents in integration on the Red Sea coast. The aim of the present study was to test integrated aquaculture of seaweed and marine fish ( Oreochromis spilurus ) for the first time in Saudi Arabia and to determine the seaweeds, Ulva lactuca and Gracilaria arcuata , biomass production and inorganic nutrient bioremediation capabilities. Results showed that G. arcuata grew at a significantly higher rate (2.71% wet weight day −1 ) than U. lactuca (1.77% wet weight day −1 ). The biomass yield (42.38 g wet weight m −2 day −1 ) and net yield (91.11 g wet weight day −1 ) of G. arcuata were also significantly higher than U. lactuca (27.39 g wet weight m −2 day −1 and 58.89 g wet weight day −1 , respectively). Gracilaria arcuata removed 0.45 g m −2 day −1 of total ammonia nitrogen (TAN) with 80.15% removal efficiency and 1.03 g m −2 day −1 of soluble phosphate with 41.06% efficiency. Ulva lactuca removed 0.42 g m −2 day −1 of TAN with 83.06% removal efficiency and 1.07 g m −2 day −1 of soluble phosphate with 41.11% efficiency. Total tissue carbon of both species reached 25.1–26.9% and nitrogen content reached 3.0–3.2% of dry weight. The C/N ratio for both seaweeds was G. arcuata has relatively higher growth potential.